-Obesity and Related Factors among Intermediate and High School Girls in Saudi Arabia schools - Case study: Al-Diriyah girl’s schools 2016-2017 - Shalabi, Maha Matouq; Ismael, Rawaa Ismael Mohamad; al-mutairi, Leena mohammed; abahussain, Hessa Abdulkareem; al saleem, Sarah ahmad; farouqi, Hanan zia allah; al qahtani, Sarah Abdullah; al nowibt, Norah saad; alsalman, Ayat Abdullah; al suheel, Asmaa abdulaziz; al harbi, Sarah; Nasser, Sarah Jameel; et al. (Journal of medical and pharmaceutical sciences, 2018)
The study aimed to determine the proportion and feature of obesity in Al-Diriyah girl’s schools in Saudi Arabia and factors related to it. An observational descriptive cross-sectional school based study. In AL- Diriyah over a one-year period (2016-2017), data will be collected from 275 schoolgirl students and it was selected by convenience technique. The results revealed that there was significant statistical finding about the association between the eating habit, sleep time and the body weight categories. Also, it shows there was P=0.0104 for family history of obesity and P=0.04 for number of the snacks per day. Moreover, there was a strong association between family history and obese girls, so obesity has a genetic effect, but the unhealthy lifestyle plays a major role, to control obesity lifestyle choices must be improved.